Uji Performansi Jangkauan Jarak Komunikasi LoRa Reyax RYLR890 - Andika, Adik Putra; Muriani, Muriani; Rusdi, Muhamad (MES Bogor, 2026)
One of the challenges of IoT applications is how to control devices remotely without using the internet. Therefore, one of the wireless technologies suitable for IoT applications is LoRa. This study aims to analyze the communication range performance of the LoRa Reyax RYLR890. The research method is experimental. The testing/measurement circuit was designed into two circuits: a transmitter circuit and a receiver circuit. In the receiver circuit, colored LEDs were added to provide information on whether they are on or off when receiving signals from the transmitter. The results of the communication range measurement of LoRa show that the maximum communication distance between the two LoRa Reyax RYLR890 modules is 1000 meters/1 kilometer. However, the most suitable location for developing the LoRa Reyax RYLR890 is an area like an airport runway, with an RSSI value of -104 dBm and an SNR value of 31 dB. This is due to the wide, long, and unobstructed geographical conditions of the area. Although the communication signal strength is considered weak/poor, the signal is clean/does not have much noise/interference, making it more stable.